The future of Afrikaans as university language within a multilingual environment: The language debate at Stellenbosch - Le Cordeur, Michael L. (L1-Educational Studies in Language and Literature, 2017)
Language is of critical importance in curriculum delivery as it determines how knowledge is received, constructed and transmitted. The hegemony of English has led to a gradual decrease in the use of Afrikaans at the historically Afrikaans universities (HAUs). This article investigates the prevailing debate about the future of Afrikaans as university language. Based on the premise that South Africa is a multilingual country with 11 official languages where most students are not Afrikaans or English speaking, the research question we asked, is whether there is still a place for Afrikaans as university language. There is a strong correlation between mother-tongue instruction and success in academic performance (Alexander, 1997; De Varennes, 2010). Yet in most South African universities English is the default language of instruction which means most South African students have to study through their second language. The article will argue that many students are academically unsuccessful because the nature of second-language learning is extremely complex (Woolfolk, 2010: 43). Based on Vygotsky's (1978) social constructivist theory and his description of language competency in a second language and the acquisition thereof, the research design will be in the form of a literature study with special focus on the language debate at Stellenbosch University. Against this background the article will motivate why a multilingual language policy is recommended.